2016
DOI: 10.1590/2317-6431-2015-1603
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de acidente vascular cerebral com enfoque em distúrbios da comunicação oral em pacientes de um hospital regional

Abstract: Purpose: To characterize patients with stroke and to establish the prevalence of oral communication disorders (CD) related by cerebrovascular accident (CVA) and the frequency of indication or request of speech therapy. Methods: A retrospective cross-sectional study from the medical report forms of 95 patients hospitalized for stroke between June 2007 and June 2008 in a regional public hospital. Results: Out of the 95 patients, 51 (53.7%) were male (mean age was 59.8 years old), 48 (59.3%) had a history of hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
2
1
0
5
Order By: Relevance
“…The most common risk factor for stroke identified in the groups was SAH, in line with data from the literature (20,28) showing a high prevalence of this condition. Despite evidence indicating a steady decline in smoking in Brazil (29) , the proportion of smokers in the sample proved high (55.5%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most common risk factor for stroke identified in the groups was SAH, in line with data from the literature (20,28) showing a high prevalence of this condition. Despite evidence indicating a steady decline in smoking in Brazil (29) , the proportion of smokers in the sample proved high (55.5%).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the clinical profile of the group studied, ischemic stroke was the most frequent type, mirroring findings reported in the literature (25)(26)(27)(28) showing this stroke subtype accounts for 70-80% of cases. The CT topodiagnostic findings for brain lesions disclosed a mixed pattern in all groups, involving cortical and/or subcortical lesions in lobes of both left and right hemispheres (Chart 1).…”
Section: Discussionsupporting
confidence: 84%
“…Discorrendo sobre o estado clínico do indivíduo com AVC, os déficits neurológicos mais frequentes são: paralisia total ou parcial do hemicorpo (hemiparesia e hemiplegia), comprometimento sensorial, cognitivo e no campo visual; hemiplegia contralateral, sendo a principal disfunção motora gerada, fazendo com que 70% dos pacientes ao receber alta hospitalar,saem com problemas relacionados a comunicação verbal e incapacidade funcional, resultando em um decaimento do grau de funcionalidade do indivíduo afetando diretamente o exercício de diversas atividades do cotidiano e de seu autocuidado. (PASSOS, CARDOSO, SCHEEREN 2017, GOULART, ALMEIDA, SILVA, OENNING, LAGN, 2016.…”
Section: Introductionunclassified
“…A study on the characterization of speech-language disorders of adult patients hospitalized after a stroke showed that no participant did speech-language therapy during hospitalization, neither were they referred to speech-language therapy after discharge; that suggests that these patients, at best, would receive integral rehabilitation care through the referral from the basic health team (18) . However, with the results obtained in this research, which concluded that 54.5% (n = 12) refer patients to speech-language rehabilitation and 27.3% request specialist orientation support for this professional, it is noticed that this is not the reality for post-stroke patients in Primary Health Care.…”
Section: Discussionmentioning
confidence: 99%